Changes in Brain Glutamate on Switching to Clozapine in Treatment-Resistant Schizophrenia. (5th January 2021) - McQueen, Grant; Sendt, Kyra-Verena; Gillespie, Amy; Avila, Alessia; Lally, John; Vallianatou, Kalliopi; Chang, Nynn; Ferreira, Diogo; Borgan, Faith; Howes, Oliver D; Barker, Gareth J; Lythgoe, David J; et al.
Abstract: It has been suggested that the antipsychotic clozapine may modulate brain glutamate, and that this effect could contribute to its efficacy in treatment-resistant schizophrenia (TRS). The aim of this study was to examine the effects of clozapine on brain glutamate in TRS longitudinally. This study examined individuals with TRS before and 12 weeks after switching from a non-clozapine antipsychotic to treatment with clozapine as part of their normal clinical care. Proton magnetic resonance spectroscopy ( 1 H-MRS) measured concentrations, corrected for voxel tissue content, of glutamate (Glucorr ), and glutamate plus glutamine (Glxcorr ) in the anterior cingulate cortex (ACC) and right caudate nucleus. Symptoms were monitored using the Positive and Negative Syndrome Scale (PANSS). Of 37 recruited patients (27 men, 39.30 years old, 84% clozapine naïve), 25 completed 1 H-MRS at both timepoints. 12 weeks of clozapine was associated with a longitudinal reduction in Glucorr in the caudate ( n = 23, F = 7.61 P = .01) but not in the ACC ( n = 24, F = 0.02, P = .59). Percentage reduction in caudate Glucorr was positively correlated with percentage improvement in symptoms (total PANSS score, n = 23, r = .42, P = .04). These findings indicate that reductions in glutamate in the caudate nucleus may contribute to symptomatic improvement during the first months of clozapine treatment.